Polarizer with a phase difference layer and image display device using the polarizer with the phase difference layer
By using a polyvinyl alcohol resin film with a dichromatic substance and adopting multi-stage stretching and drying shrinkage treatment, the problem of reducing optical characteristics of the polarizing film after thinning in the prior art is solved, and an efficient polarizer development with a phase difference layer is achieved.
Patent Information
- Application Number
- CN202411031153.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-21
- Filing Date
- 2019-10-12
- Publication Date
- 2025-06-17
- Estimated Expiration
- 2039-10-12
AI Technical Summary
During the thinning process of the conventional polarizer with a phase difference layer, the optical characteristics of the polarizing film are reduced, resulting in a decrease in operability and warping of the image display device.
A polarizing film made of a polyvinyl alcohol resin film containing a dichromatic substance was obtained by assisting stretching in a gas atmosphere, stretching in an aqueous solution, and drying and shrinking treatment of a heating roller, and a polarizing film having a thickness of 8 μm or less, a monomer transmittance of 43.5% or more, and a polarization degree of 99.940% or more was obtained.
A polarizer with a phase difference layer with a thin, excellent processing properties and excellent optical characteristics is realized, thereby avoiding warping and degradation of the image display device.
Smart Images

Figure CN118837988B_ABST
Abstract
Description
[0001] This application is a divisional application of an application with an application date of October 12, 2019, an application number of 201910970693.X, and an invention title of "Polarizing Plate with Phase Difference Layer and Image Display Device Using the Same". Technical Field
[0002] The present invention relates to a polarizing plate with a phase difference layer and an image display device using the same. Background Art
[0003] In recent years, image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices (for example, organic EL display devices, inorganic EL display devices) have been rapidly popularized. In image display devices, polarizing plates and retardation plates are typically used. In actual use, a polarizing plate with a phase difference layer in which a polarizing plate and a retardation plate are integrated is widely used (for example, Patent Document 1). Recently, as the demand for thinning of image display devices has increased, the demand for thinning of polarizing plates with a phase difference layer has also increased. In addition, in recent years, the demand for curved image display devices and / or flexible or bendable image display devices has been increasing, and further thinning and further softening are also required for polarizing plates and polarizing plates with a phase difference layer. For the purpose of thinning a polarizing plate with a phase difference layer, thinning of a protective layer and a retardation film of a polarizing film that contributes greatly to the thickness has been carried out. However, if the protective layer and the retardation film are thinned, the influence of shrinkage of the polarizing film becomes relatively large, and problems such as warping of the image display device and a decrease in the operability of the polarizing plate with a phase difference layer occur.
[0004] In order to solve the above problems, it is necessary to thin the polarizing film as well. However, if the thickness of the polarizing film is simply reduced, the optical properties deteriorate. More specifically, one or both of the polarization degree and the monomer transmittance, which have a trade-off relationship, are reduced to an unacceptable level for practical use. As a result, the optical properties of the polarizing plate with a phase difference layer also become insufficient.
[0005] Prior Art Documents
[0006] Patent Documents
[0007] Patent Document 1: Japanese Patent No. 3325560 Gazette Summary of the Invention
[0008] Problems to be Solved by the Invention
[0009] The present invention is made to solve the above-mentioned existing problems, and its main object is to provide a polarizing plate with a phase difference layer that is thin, has excellent processability, and has excellent optical properties.
[0010] Method for solving problems
[0011] The polarizing plate with a retardation layer of the present invention has a polarizing plate and a retardation layer. The polarizing plate includes a polarizing film and a protective layer provided on at least one side of the polarizing film. The polarizing film is composed of a polyvinyl alcohol resin film containing a dichroic substance, has a thickness of 8 μm or less, a monomer transmittance of 43.5% or more, and a degree of polarization of 99.940% or more. The retardation layer is an alignment fixing layer of a liquid crystal compound.
[0012] In one embodiment, the unit weight of the above-mentioned polarizing plate with a retardation layer is 6.5 mg / cm 2 or less.
[0013] In one embodiment, the total thickness of the above-mentioned polarizing plate with a retardation layer is 60 μm or less.
[0014] In one embodiment, the above-mentioned retardation layer is a single layer of an alignment fixing layer of a liquid crystal compound. Re(550) of this retardation layer is 100 nm to 190 nm, and the angle formed by the slow axis of this retardation layer and the absorption axis of the above-mentioned polarizing film is 40° to 50°.
[0015] In one embodiment, the above-mentioned retardation layer has a laminated structure of an alignment fixing layer of a first liquid crystal compound and an alignment fixing layer of a second liquid crystal compound; Re(550) of the alignment fixing layer of the first liquid crystal compound is 200 nm to 300 nm, and the angle formed by its slow axis and the absorption axis of the above-mentioned polarizing film is 10° to 20°; Re(550) of the alignment fixing layer of the second liquid crystal compound is 100 nm to 190 nm, and the angle formed by its slow axis and the absorption axis of the polarizing film is 70° to 80°.
[0016] In one embodiment, the maximum value and the minimum value of the monomer transmittance of the above-mentioned polarizing film in a region of 50 cm 2 differ by 0.15% or less.
[0017] In one embodiment, the width of the above-mentioned polarizing plate with a retardation layer is 1000 mm or more, and the difference between the maximum value and the minimum value of the monomer transmittance at positions along the width direction of the above-mentioned polarizing film is 0.3% or less.
[0018] In one embodiment, the monomer transmittance of the above-mentioned polarizing film is 44.0% or less, and the degree of polarization is 99.990% or less.
[0019] In one embodiment, the above-mentioned polarizing plate with a retardation layer further has another retardation layer outside the above-mentioned retardation layer, and the refractive index characteristics of this other retardation layer show a relationship of nz > nx = ny.
[0020] In one embodiment, the polarizer with a retardation layer further has a conductive layer or an isotropic substrate with a conductive layer on the outside of the retardation layer.
[0021] According to another aspect of the present invention, there is provided an image display device including the above-described polarizer with a retardation layer.
[0022] In one embodiment, the image display device is an organic electroluminescent display device or an inorganic electroluminescent display device.
[0023] Effects of the Invention
[0024] According to the present invention, by combining the addition of a halide (representatively potassium iodide) to a polyvinyl alcohol (PVA)-based resin, two-stage stretching including stretching in a gas atmosphere and stretching in an aqueous solution, and drying and shrinkage using a heating roll, a polarizing film that is thin and has very excellent optical characteristics can be obtained. By using such a polarizing film, a polarizer with a retardation layer that is thin, has excellent processability, and has excellent optical characteristics can be realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a schematic cross-sectional view of a polarizer with a retardation layer according to one embodiment of the present invention.
[0026] Figure 2 is a schematic cross-sectional view of a polarizer with a retardation layer according to another embodiment of the present invention.
[0027] Figure 3 is a schematic cross-sectional view of a polarizer with a retardation layer according to still another embodiment of the present invention.
[0028] Figure 4 is a schematic diagram showing an example of a drying and shrinkage process using a heating roll in the method for manufacturing a polarizing film for a polarizer with a retardation layer of the present invention.
[0029] REFERENCE SIGNS
[0030] 10 Polarizer
[0031] 11 Polarizing film
[0032] 12 First protective layer
[0033] 13 Second protective layer
[0034] 20 Retardation layer
[0035] 100 Polarizer with a retardation layer
[0036] 101 Polarizer with a retardation layer
[0037] 102 Polarizer with a phase difference layer Detailed implementation manners
[0038] Hereinafter, the implementation manners of the present invention will be described, but the present invention is not limited to these implementation manners.
[0039] (Definition of terms and symbols)
[0040] The definitions of the terms and symbols in this specification are as follows.
[0041] (1) Refractive indices (nx, ny, nz)
[0042] "nx" is the refractive index in the direction where the in-plane refractive index reaches the maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction orthogonal to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction.
[0043] (2) In-plane phase difference (Re)
[0044] "Re(λ)" is the in-plane phase difference measured with light of wavelength λ nm at 23°C. For example, "Re(550)" is the in-plane phase difference measured with light of wavelength 550 nm at 23°C. When the thickness of the layer (film) is set to d (nm), Re(λ) can be obtained by the formula: Re(λ) = (nx - ny) × d.
[0045] (3) Phase difference in the thickness direction (Rth)
[0046] "Rth(λ)" is the phase difference in the thickness direction measured with light of wavelength λ nm at 23°C. For example, "Rth(550)" is the phase difference in the thickness direction measured with light of wavelength 550 nm at 23°C. When the thickness of the layer (film) is set to d (nm), Rth(λ) can be obtained by the formula: Rth(λ) = (nx - nz) × d.
[0047] (4) Nz coefficient
[0048] The Nz coefficient is obtained by Nz = Rth / Re.
[0049] (5) Angle
[0050] In this specification, when an angle is mentioned, the angle includes both clockwise and counterclockwise with respect to the reference direction. Therefore, for example, "45°" means ±45°.
[0051] A. Overall structure of the polarizer with a phase difference layer
[0052] Figure 1It is a schematic cross-sectional view of a polarizing plate with a phase difference layer according to an embodiment of the present invention. The polarizing plate 100 with a phase difference layer in this embodiment has a polarizer 10 and a phase difference layer 20. The polarizer 10 includes: a polarizing film 11, a first protective layer 12 disposed on one side of the polarizing film 11, and a second protective layer 13 disposed on the other side of the polarizing film 11. Depending on the purpose, one of the first protective layer 12 and the second protective layer 13 can be omitted. For example, when the phase difference layer 20 can also function as a protective layer of the polarizing film 11, the second protective layer 13 can be omitted. In an embodiment of the present invention, the polarizing film is composed of a polyvinyl alcohol-based resin film containing a dichroic substance. The thickness of the polarizing film is 8 μm or less, the monomer transmittance is 43.5% or more, and the degree of polarization is 99.940% or more.
[0053] As Figure 2 shown, in a polarizing plate 101 with a phase difference layer according to another embodiment, other phase difference layers 50 and / or a conductive layer or an isotropic substrate 60 with a conductive layer can be provided. The other phase difference layers 50 and the conductive layer or the isotropic substrate 60 with a conductive layer are typically provided on the outside of the phase difference layer 20 (the side opposite to the polarizer 10). The refractive index characteristics of the other phase difference layers typically show a relationship of nz > nx = ny. Typically, the other phase difference layers 50 and the conductive layer or the isotropic substrate 60 with a conductive layer are provided in sequence from the side of the phase difference layer 20. Typically, the other phase difference layers 50 and the conductive layer or the isotropic substrate 60 with a conductive layer are arbitrary layers provided as needed, and either one or both of them can be omitted. It should be noted that, for convenience, the phase difference layer 20 is sometimes referred to as the first phase difference layer, and the other phase difference layers 50 are sometimes referred to as the second phase difference layer. It should be noted that in the case of providing a conductive layer or an isotropic substrate with a conductive layer, the polarizing plate with a phase difference layer can be applied to a so-called in-cell touch panel type input display device in which a touch sensor is introduced between an image display unit (such as an organic EL unit) and the polarizing plate.
[0054] In an embodiment of the present invention, the first phase difference layer 20 is an alignment fixing layer of a liquid crystal compound. The first phase difference layer 20 can be a single layer of an alignment fixing layer as Figure 1 and Figure 2 shown, or can have a laminated structure of a first alignment fixing layer 21 and a second alignment fixing layer 22 as Figure 3 shown.
[0055] The above embodiments can be appropriately combined, or those skilled in the art can make obvious changes to the components in the above embodiments. For example, it can be in Figure 3The polarizer 102 with a phase difference layer is provided with a second phase difference layer 50 and / or a conductive layer or an isotropic substrate 60 with a conductive layer. In addition, for example, the configuration in which the isotropic substrate 60 with a conductive layer is provided outside the second phase difference layer 50 can be replaced with an optically equivalent configuration (for example, a laminate of the second phase difference layer and the conductive layer).
[0056] The polarizer with a phase difference layer according to an embodiment of the present invention may further contain other phase difference layers. The optical properties (for example, refractive index properties, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement position, etc. of the other phase difference layers can be appropriately set according to the purpose.
[0057] The polarizer with a phase difference layer of the present invention can be in a sheet shape or a long strip shape. In this specification, "long strip shape" means an elongated shape in which the length is sufficiently long relative to the width. For example, it includes an elongated shape in which the length is 10 times or more, preferably 20 times or more, relative to the width. The polarizer with a phase difference layer in a long strip shape can be wound into a roll shape.
[0058] In actual use, an adhesive layer (not shown) can be provided on the side of the phase difference layer opposite to the polarizer, and the polarizer with a phase difference layer can be adhered to the image display unit. In addition, it is preferable that a release film is temporarily adhered to the surface of the adhesive layer until the polarizer with a phase difference layer is put into use. By temporarily adhering the release film, the adhesive layer can be protected and a roll can be formed.
[0059] The total thickness of the polarizer with a phase difference layer is preferably 60 μm or less, more preferably 55 μm or less, further preferably 50 μm or less, and particularly preferably 40 μm or less. The lower limit of the total thickness can be, for example, 28 μm. According to an embodiment of the present invention, a very thin polarizer with a phase difference layer can be achieved in this way. Such a polarizer with a phase difference layer can have very excellent flexibility and bending durability. Such a polarizer with a phase difference layer can be particularly suitably used for a curved image display device and / or a bendable or foldable image display device. It should be noted that the total thickness of the polarizer with a phase difference layer refers to the total thickness of all the layers constituting the polarizer with a phase difference layer except for the adhesive layer used to bond the polarizer to an external adherend such as a panel or glass (that is, the total thickness of the polarizer with a phase difference layer does not include the thickness of the adhesive layer used to adhere the polarizer with a phase difference layer to an adjacent member such as an image display unit and the release film that can be temporarily adhered to its surface).
[0060] The unit weight of the polarizer with a phase difference layer according to an embodiment of the present invention is, for example, 6.5 mg / cm 2 Hereinafter, it is preferably 2.0 mg / cm 2 ~6.0 mg / cm 2 and more preferably 3.0 mg / cm2 ~5.5 mg / cm 2 , and more preferably 3.5 mg / cm 2 ~5.0 mg / cm 2 . When the display panel is thin, the panel may be slightly deformed due to the weight of the polarizer with the retardation layer, and there is a concern about display defects. However, according to the polarizer with the retardation layer having a unit weight of 6.5 mg / cm 2 or less, such panel deformation can be prevented. In addition, the polarizer with the retardation layer having the above unit weight has good processability even in the case of thinning, and can exhibit very excellent flexibility and bending durability.
[0061] Hereinafter, the constituent elements of the polarizer with the retardation layer will be described in more detail.
[0062] B. Polarizer
[0063] B-1. Polarization film
[0064] As described above, the thickness of the polarization film 11 is 8 μm or less, the monomer transmittance is 43.5% or more, and the degree of polarization is 99.940% or more. Generally, there is a trade-off relationship between the monomer transmittance and the absorbance. If the monomer transmittance is increased, the absorbance will decrease, and if the absorbance is increased, the monomer transmittance will decrease. Therefore, it has been difficult to practically use a thin polarization film that satisfies the optical characteristics of a monomer transmittance of 43.5% or more and a degree of polarization of 99.940% or more. It is one of the features of the present invention to use a thin polarization film having excellent optical characteristics such as a monomer transmittance of 43.5% or more and a degree of polarization of 99.940% or more, and in which the deviation of the optical characteristics is suppressed.
[0065] The thickness of the polarization film is preferably 1 μm to 8 μm, more preferably 1 μm to 7 μm, and further preferably 2 μm to 5 μm.
[0066] The polarization film preferably exhibits absorption dichroism at any wavelength in the wavelength range of 380 nm to 780 nm. The monomer transmittance of the polarization film is preferably 44.0% or less. The degree of polarization of the polarization film is preferably 99.950% or more, more preferably 99.960% or more. On the other hand, the degree of polarization is preferably 99.990% or less. The above monomer transmittance is typically the Y value obtained by measuring with a UV-visible spectrophotometer and performing visibility correction. The above degree of polarization is typically obtained based on the parallel transmittance Tp and the orthogonal transmittance Tc obtained by measuring with a UV-visible spectrophotometer and performing visibility correction, and is calculated by the following formula.
[0067] Degree of polarization (%) = {(Tp - Tc) / (Tp + Tc)} 1 / 2 × 100
[0068] In one embodiment, the transmittance of a thin polarizing film with a thickness of 8 μm or less is typically measured using an ultraviolet-visible spectrophotometer with a laminate of a polarizing film (refractive index of the surface: 1.53) and a protective film (refractive index: 1.50) as the measurement object. Depending on the refractive index of the surface of the polarizing film and / or the refractive index of the surface in contact with the air interface of the protective film, the reflectance at the interface of each layer changes, and as a result, the measured value of the transmittance may change. Therefore, for example, when using a protective film with a refractive index other than 1.50, the measured value of the transmittance can be corrected according to the refractive index of the surface in contact with the air interface of the protective film. Specifically, the correction value C of the transmittance is represented by the following formula using the reflectance R1 (transmittance axis reflectance) of polarized light parallel to the transmittance axis at the interface between the protective film and the air layer.
[0069] C = R1 - R0
[0070] R0 = ((1.50 - 1) 2 / (1.50 + 1) 2 ) × (T1 / 100)
[0071] R1 = ((n1 - 1) 2 / (n1 + 1) 2 ) × (T1 / 100)
[0072] Here, R0 is the transmittance axis reflectance when using a protective film with a refractive index of 1.50, n1 is the refractive index of the used protective film, and T1 is the transmittance of the polarizing film. For example, when using a substrate (cycloolefin film, film with a hard coat, etc.) with a surface refractive index of 1.53 as the protective film, the correction amount C becomes approximately 0.2%. In this case, by adding 0.2% to the transmittance obtained by measurement, the transmittance can be converted to the case of using a protective film with a surface refractive index of 1.50. It should be noted that according to the calculation based on the above formula, the change amount of the correction value C when the transmittance T1 of the polarizing film changes by 2% is 0.03% or less, and the influence of the transmittance of the polarizing film on the value of the correction value C is limited. In addition, when the protective film has absorption other than surface reflection, appropriate correction can be made according to the absorption amount.
[0073] In one embodiment, the width of the polarizer with a retardation layer is 1000 mm or more, and thus the width of the polarizing film is also 1000 mm or more. In this case, the difference (D1) between the maximum value and the minimum value of the monomer transmittance at positions along the width direction of the polarizing film is preferably 0.3% or less, more preferably 0.25% or less, and still more preferably 0.2% or less. The smaller D1 is, the more preferable it is, and the lower limit of D1 can be, for example, 0.01%. When D1 is within the above range, a polarizer with a retardation layer having excellent optical characteristics can be industrially manufactured. In another embodiment, the difference (D2) between the maximum value and the minimum value of the monomer transmittance of the polarizing film within a region of 50 cm 2 is preferably 0.15% or less, more preferably 0.1% or less, and still more preferably 0.08% or less. The smaller D2 is, the more preferable it is, and the lower limit of D2 can be, for example, 0.01%. When D2 is within the above range, uneven brightness in the display screen can be suppressed when the polarizer with a retardation layer is used in an image display device.
[0074] As the polarizing film, any suitable polarizing film can be used. Typically, the polarizing film can be made of a laminate of two or more layers.
[0075] As a specific example of the polarizing film obtained using a laminate, a polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be cited. The polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be manufactured by the following method: for example, a PVA-based resin solution is coated on the resin substrate and dried to form a PVA-based resin layer on the resin substrate, and a laminate of the resin substrate and the PVA-based resin layer is obtained; the laminate is stretched and dyed to form the PVA-based resin layer into a polarizing film. In the present embodiment, stretching typically includes immersing the laminate in an aqueous boric acid solution for stretching. In addition, stretching may further include stretching the laminate in a gas atmosphere at a high temperature (for example, 95°C or higher) before stretching in the aqueous boric acid solution as needed. The obtained laminate of the resin substrate / polarizing film can be used directly (that is, the resin substrate can be used as a protective layer of the polarizing film), or the resin substrate can be peeled off from the laminate of the resin substrate / polarizing film, and any suitable protective layer according to the purpose can be laminated on the peeled surface for use. The details of such a method for manufacturing a polarizing film are described in, for example, Japanese Patent Application Laid-Open No. 2012-73580. The entire disclosure of this publication can be incorporated herein by reference.
[0076] Typical methods for manufacturing a polarizing film include: forming a polyvinyl alcohol resin layer containing a halide and a polyvinyl alcohol resin on one side of a strip-shaped thermoplastic resin substrate to form a laminate; and successively performing an auxiliary stretching treatment, a dyeing treatment, a stretching treatment in an aqueous solution, and a drying shrinkage treatment in which the laminate is heated while being transported in the length direction so as to shrink by 2% or more in the width direction. Thereby, a polarizing film having a thickness of 8 μm or less, a monomer transmittance of 43.5% or more, a degree of polarization of 99.940% or more, excellent optical properties, and suppressed deviation of optical properties can be provided. That is, by introducing auxiliary stretching, even when PVA is coated on a thermoplastic resin, the crystallinity of PVA can be improved, and high optical properties can be achieved. In addition, by simultaneously improving the orientation of PVA in advance, problems such as a decrease in the orientation of PVA and dissolution can be prevented when immersed in water in subsequent dyeing and stretching processes, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation disorder and the decrease in orientation of polyvinyl alcohol molecules can be suppressed as compared with the case where the PVA-based resin layer does not contain a halide. Thereby, the optical properties of the polarizing film obtained by a treatment process in which the laminate is immersed in a liquid such as a dyeing treatment and a stretching treatment in an aqueous solution can be improved. In addition, by performing a drying shrinkage treatment to shrink the laminate in the width direction, the optical properties can be improved.
[0077] B-2. Protective layer
[0078] The first protective layer 12 and the second protective layer 13 can be formed of any suitable film that can be used as a protective layer of the polarizing film. Specific examples of the material that is the main component of the film include transparent resins such as cellulose resins such as triacetyl cellulose (TAC), polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, polynorbornenes, polyolefins, (meth)acrylic acids, and acetates. In addition, thermosetting resins or ultraviolet curable resins such as (meth)acrylic acids, urethanes, (meth)acrylic urethanes, epoxies, and silicones can also be mentioned. In addition to these, glassy polymers such as siloxane polymers can also be mentioned. In addition, a polymer film described in Japanese Patent Laid-Open No. 2001-343529 (WO01 / 37007) can also be used. As the material of the film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain can be used. Specific examples include a resin composition having an alternating copolymer formed of isobutene and N-methylmaleimide and an acrylonitrile-styrene copolymer. The polymer film can be, for example, an extruded product of the above resin composition.
[0079] The polarizer with a phase difference layer of the present invention is typically disposed on the visible side of an image display device as described later, and the first protective layer 12 is typically disposed on its visible side. Therefore, surface treatments such as hard coating treatment, antireflection treatment, antiadhesion treatment, antiglare treatment, etc. can be performed on the first protective layer 12 as needed. In addition / Or, when visually recognized through polarized sunglasses, a treatment for improving visual recognition (typically imparting an (elliptical) polarization function, imparting an ultrahigh phase difference) can be performed on the first protective layer 12 as needed. By performing such a treatment, excellent visual recognition can be achieved even when the display screen is visually recognized through a polarizing lens such as polarized sunglasses. Therefore, the polarizer with a phase difference layer can also be applied to an image display device that can be used outdoors.
[0080] The thickness of the first protective layer is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and still more preferably 10 μm to 30 μm. It should be noted that in the case of performing surface treatment, the thickness of the outer protective layer is the thickness including the thickness of the surface treatment layer.
[0081] In one embodiment, the second protective layer 13 is preferably optically isotropic. In this specification, "being optically isotropic" means that the in-plane phase difference Re(550) is 0 nm to 10 nm and the thickness-direction phase difference Rth(550) is -10 nm to +10 nm. In one embodiment, the second protective layer 13 can be a phase difference layer having any appropriate phase difference value. In this case, the in-plane phase difference Re(550) of the phase difference layer is, for example, 110 nm to 150 nm. The thickness of the second protective layer is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and still more preferably 10 μm to 30 μm. From the viewpoints of thinning and lightening, it is preferable that the second protective layer can be omitted.
[0082] B-3. Manufacturing Method of Polarizing Film
[0083] A polarizing film can be produced by a method including the following steps: for example, forming a polyvinyl alcohol resin layer (PVA resin layer) containing a halide and a polyvinyl alcohol resin (PVA resin) on one side of a strip-shaped thermoplastic resin substrate to form a laminate; and successively performing an auxiliary stretching treatment in a gas atmosphere, a dyeing treatment, a stretching treatment in an aqueous solution, and a drying shrinkage treatment in which the laminate is heated while being transported in the length direction so that it shrinks by 2% or more in the width direction. With respect to 100 parts by weight of the PVA resin, the content of the halide in the PVA resin layer is preferably 5 to 20 parts by weight. The drying shrinkage treatment is preferably performed using a heating roller, and the temperature of the heating roller is preferably 60°C to 120°C. The shrinkage rate of the laminate in the width direction by the drying shrinkage treatment is preferably 2% or more. According to such a manufacturing method, the polarizing film described in item B-1 above can be obtained. In particular, a laminate including a PVA resin layer containing a halide is produced, the stretching of the laminate is subjected to multi-stage stretching including auxiliary stretching in a gas atmosphere and stretching in an aqueous solution, and the stretched laminate is heated using a heating roller, whereby a polarizing film having excellent optical properties (representatively, monomer transmittance and degree of polarization) and with the deviation of the optical properties suppressed can be obtained. Specifically, by using a heating roller in the drying shrinkage treatment step, the laminate can be uniformly shrunk as a whole while being transported. Thereby, not only can the optical properties of the obtained polarizing film be improved, but also a polarizing film with excellent optical properties can be stably produced, and the deviation of the optical properties (especially monomer transmittance) of the polarizing film can be suppressed.
[0084] B-3-1. Fabrication of Laminate
[0085] As a method for fabricating a laminate of a thermoplastic resin substrate and a PVA resin layer, any suitable method can be adopted. It is preferable to coat a coating liquid containing a halide and a PVA resin on the surface of the thermoplastic resin substrate and dry it, thereby forming a PVA resin layer on the thermoplastic resin substrate. As described above, with respect to 100 parts by weight of the PVA resin, the content of the halide in the PVA resin layer is preferably 5 to 20 parts by weight.
[0086] As a coating method for the coating liquid, any suitable method can be adopted. Examples include: roll coating method, spin coating method, wire-wound bar coating method, dip coating method, die coating method, curtain coating method, spraying method, doctor blade coating method (such as knife coating method), etc. The coating / drying temperature of the above coating liquid is preferably 50°C or higher.
[0087] The thickness of the PVA resin layer is preferably 3 μm to 40 μm, more preferably 3 μm to 20 μm.
[0088] Before forming the PVA-based resin layer, the thermoplastic resin substrate may be subjected to surface treatment (e.g., corona treatment, etc.), and an easy-adhesion layer may be formed on the thermoplastic resin substrate. By performing such treatment, the adhesion between the thermoplastic resin substrate and the PVA-based resin layer can be improved.
[0089] B-3-1-1. Thermoplastic resin substrate
[0090] The thickness of the thermoplastic resin substrate is preferably 20 μm to 300 μm, more preferably 50 μm to 200 μm. When it is less than 20 μm, there is a concern that it is difficult to form the PVA-based resin layer. When it exceeds 300 μm, for example, in the stretching treatment in the aqueous solution described later, the thermoplastic resin substrate takes a long time to absorb water, and there is a concern that a too large load is required for stretching.
[0091] The water absorption rate of the thermoplastic resin substrate is preferably 0.2% or more, more preferably 0.3% or more. When the thermoplastic resin substrate absorbs water, the water acts like a plasticizer and can be plasticized. As a result, the tensile stress can be significantly reduced, and stretching can be performed at a high magnification. On the other hand, the water absorption rate of the thermoplastic resin substrate is preferably 3.0% or less, more preferably 1.0% or less. By using such a thermoplastic resin substrate, it is possible to prevent adverse conditions such as a significant decrease in the dimensional stability of the thermoplastic resin substrate during manufacturing and deterioration of the appearance of the obtained polarizing film. In addition, it is possible to prevent the substrate from breaking during stretching in the aqueous solution and the PVA-based resin layer from peeling off from the thermoplastic resin substrate. It should be noted that the water absorption rate of the thermoplastic resin substrate can be adjusted, for example, by introducing a modified group into the constituent material. The water absorption rate is a value obtained in accordance with JIS K 7209.
[0092] The glass transition temperature (Tg) of the thermoplastic resin substrate is preferably 120°C or lower. By using such a thermoplastic resin substrate, crystallization of the PVA-based resin layer can be suppressed, and the stretchability of the laminate can be sufficiently ensured. In addition, considering the plasticization of the thermoplastic resin substrate using water and good stretching in the aqueous solution, it is more preferably 100°C or lower, further preferably 90°C or lower. On the other hand, the glass transition temperature of the thermoplastic resin substrate is preferably 60°C or higher. By using such a thermoplastic resin substrate, it is possible to prevent adverse conditions such as deformation (e.g., occurrence of unevenness, slack, wrinkles, etc.) of the thermoplastic resin substrate during coating / drying of the above-mentioned coating liquid containing the PVA-based resin, and a laminate can be well produced. In addition, stretching of the PVA-based resin layer can be performed well at an appropriate temperature (e.g., around 60°C). It should be noted that the glass transition temperature (Tg) of the thermoplastic resin substrate can be adjusted, for example, by using a crystallization material into which a modified group is introduced into the constituent material and heating. The glass transition temperature (Tg) is a value obtained in accordance with JIS K 7121.
[0093] As a constituent material of the thermoplastic resin substrate, any suitable thermoplastic resin can be used. Examples of the thermoplastic resin include ester resins such as polyethylene terephthalate resins, cycloolefin resins such as norbornene resins, olefin resins such as polypropylene, polyamide resins, polycarbonate resins, copolymer resins thereof, and the like. Among these, norbornene resins and amorphous polyethylene terephthalate resins are preferred.
[0094] In one embodiment, it is preferable to use an amorphous (uncrystallized) polyethylene terephthalate resin. Among them, it is particularly preferable to use an amorphous (difficult to crystallize) polyethylene terephthalate resin. Specific examples of the amorphous polyethylene terephthalate resin include copolymers further containing isophthalic acid and / or cyclohexanedicarboxylic acid as dicarboxylic acids, and copolymers further containing cyclohexanedimethanol and diethylene glycol as diols.
[0095] In a preferred embodiment, the thermoplastic resin substrate is composed of a polyethylene terephthalate resin having an isophthalic acid unit. This is because such a thermoplastic resin substrate has very excellent stretchability and can suppress crystallization during stretching. It is considered that by introducing the isophthalic acid unit, a large bend can be imparted to the main chain. The polyethylene terephthalate resin has a terephthalic acid unit and an ethylene glycol unit. The content ratio of the isophthalic acid unit is preferably 0.1 mol% or more, more preferably 1.0 mol% or more, based on the total of all repeating units. This is because a thermoplastic resin substrate with very excellent stretchability can be obtained. On the other hand, the content ratio of the isophthalic acid unit is preferably 20 mol% or less, more preferably 10 mol% or less, based on the total of all repeating units. By setting the content ratio in this way, the crystallinity can be improved well in the drying shrinkage treatment described later.
[0096] The thermoplastic resin substrate can be pre-stretched (before forming the PVA resin layer). In one embodiment, the long strip-shaped thermoplastic resin substrate can be stretched in the transverse direction. The transverse direction is preferably a direction orthogonal to the stretching direction of the laminate described later. It should be noted that in this specification, "orthogonal" means including substantially orthogonal cases. Here, "substantially orthogonal" means including cases of 90° ± 5.0°, preferably 90° ± 3.0°, and more preferably 90° ± 1.0°.
[0097] The stretching temperature of the thermoplastic resin substrate is preferably Tg - 10°C to Tg + 50°C with respect to the glass transition temperature (Tg). The stretching ratio of the thermoplastic resin substrate is preferably 1.5 times to 3.0 times.
[0098] As a method for stretching a thermoplastic resin substrate, any suitable method can be adopted. Specifically, it can be fixed-end stretching or free-end stretching. The stretching method can be dry or wet. The stretching of the thermoplastic resin substrate can be carried out in one stage or in multiple stages. In the case of multiple-stage stretching, the above-mentioned stretching ratio is the product of the stretching ratios of each stage.
[0099] B-3-1-2. Coating liquid
[0100] As described above, the coating liquid contains a halide and a PVA-based resin. Representative examples of the above coating liquid can be a solution obtained by dissolving the above halide and the above PVA-based resin in a solvent. Examples of the solvent include: water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, amines such as ethylenediamine and diethylenetriamine. They can be used alone or two or more of them can be used in combination. Among these, water is preferred. With respect to 100 parts by weight of the solvent, the concentration of the PVA-based resin in the solution is preferably 3 parts by weight to 20 parts by weight. If the resin concentration is such, a uniform coating film that adheres to the thermoplastic resin substrate can be formed. With respect to 100 parts by weight of the PVA-based resin, the content of the halide in the coating liquid is preferably 5 parts by weight to 20 parts by weight.
[0101] Additives can be incorporated into the coating liquid. Examples of the additives include: plasticizers, surfactants, etc. Examples of the plasticizer include: polyhydric alcohols such as ethylene glycol and glycerol. Examples of the surfactant include: nonionic surfactants. These additives are used for the purpose of further improving the uniformity, dyeability, and stretchability of the obtained PVA-based resin layer.
[0102] As the above PVA-based resin, any suitable resin can be adopted. For example, polyvinyl alcohol and ethylene-vinyl alcohol copolymer can be cited. Polyvinyl alcohol can be obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer is obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of the PVA-based resin is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The saponification degree can be determined according to JIS K 6726-1994. By using a PVA-based resin with such a saponification degree, a polarizing film with excellent durability can be obtained. In the case where the saponification degree is too high, there is a concern of gelation.
[0103] The average degree of polymerization of the PVA-based resin can be appropriately selected according to the purpose. The average degree of polymerization is usually 1000 to 10,000, preferably 1200 to 4500, and more preferably 1500 to 4300. It should be noted that the average degree of polymerization can be determined according to JIS K 6726-1994.
[0104] As the above-mentioned halide, any appropriate halide can be used. For example, iodides and sodium chloride can be mentioned. As iodides, for example, potassium iodide, sodium iodide, and lithium iodide can be mentioned. Among these, potassium iodide is preferred.
[0105] The amount of the halide in the coating liquid is preferably 5 to 20 parts by weight with respect to 100 parts by weight of the PVA-based resin, and more preferably 10 to 15 parts by weight with respect to 100 parts by weight of the PVA-based resin. When the amount of the halide exceeds 20 parts by weight with respect to 100 parts by weight of the PVA-based resin, there is a case where the halide oozes out and the finally obtained polarizing film becomes cloudy.
[0106] Generally, by stretching the PVA-based resin layer, the orientation of the polyvinyl alcohol molecules in the PVA-based resin is improved. However, if the stretched PVA-based resin layer is immersed in a liquid containing water, there is a case where the orientation of the polyvinyl alcohol molecules is disordered and the orientation is lowered. In particular, when a laminate of a thermoplastic resin substrate and a PVA-based resin layer is stretched in a boric acid aqueous solution, when the above laminate is stretched in the boric acid aqueous solution at a relatively high temperature in order to stabilize the stretching of the thermoplastic resin substrate, the tendency of the above-mentioned degree of orientation to decrease is remarkable. For example, the stretching of the PVA film monomer in the boric acid aqueous solution is usually carried out at 60 °C. In contrast, the stretching of the laminate of A-PET (thermoplastic resin substrate) and the PVA-based resin layer is carried out at a high temperature such as around 70 °C. In this case, the orientation of PVA at the initial stage of stretching decreases before increasing through stretching in the aqueous solution. In contrast, by producing a laminate of a PVA-based resin layer containing a halide and a thermoplastic resin substrate, and performing high-temperature stretching (auxiliary stretching) in the air before stretching the laminate in the boric acid aqueous solution, the crystallization of the PVA-based resin in the PVA-based resin layer of the laminate after the auxiliary stretching can be promoted. As a result, when the PVA-based resin layer is immersed in a liquid, compared with the case where the PVA-based resin layer does not contain a halide, the disorder of the orientation of the polyvinyl alcohol molecules and the decrease in the orientation can be suppressed. Thereby, the optical properties of the polarizing film obtained through treatment processes such as dyeing treatment and stretching treatment in an aqueous solution and immersing the laminate in a liquid can be improved.
[0107] B-3-2. Auxiliary stretching treatment in a gas atmosphere
[0108] In particular, in order to obtain high optical properties, a two-stage stretching method that combines dry stretching (auxiliary stretching) and stretching in an aqueous boric acid solution is selected. By introducing auxiliary stretching as in the two-stage stretching, stretching can be performed while suppressing the crystallization of the thermoplastic resin substrate, and the problem of reduced stretchability due to excessive crystallization of the thermoplastic resin substrate during subsequent stretching in the aqueous boric acid solution can be solved, and the laminate can be stretched at a higher magnification. In addition, when a PVA-based resin is coated on the thermoplastic resin substrate, in order to suppress the influence of the glass transition temperature of the thermoplastic resin substrate, compared with the case of coating a PVA-based resin on a metal drum in general, the coating temperature needs to be lowered. As a result, there will be problems such as relatively reduced crystallization of the PVA-based resin and insufficient optical properties. In contrast, by introducing auxiliary stretching, even when a PVA-based resin is coated on the thermoplastic resin, the crystallinity of the PVA-based resin can be increased, and high optical properties can be achieved. In addition, by simultaneously improving the orientation of the PVA-based resin in advance, problems such as a decrease in the orientation of the PVA-based resin and dissolution when immersed in water during subsequent dyeing and stretching processes can be prevented, and high optical properties can be achieved.
[0109] The stretching method of auxiliary stretching in a gas atmosphere can be fixed-end stretching (for example, a method of stretching using a tenter), or free-end stretching (for example, a method of performing unidirectional stretching by passing the laminate between rolls with different circumferential speeds). In order to obtain high optical properties, free-end stretching can be actively adopted. In one embodiment, the stretching treatment in a gas atmosphere includes a heating roll stretching step of stretching the laminate in the length direction while stretching it by the difference in circumferential speed between heating rolls. The stretching treatment in a gas atmosphere typically includes a zone stretching step and a heating roll stretching step. It should be noted that the order of the zone stretching step and the heating roll stretching step is not limited, and the zone stretching step can be performed first, or the heating roll stretching step can be performed first. The zone stretching step can be omitted. In one embodiment, the zone stretching step and the heating roll stretching step are performed in sequence. In addition, in another embodiment, in a tenter, the film end is held, and the distance between the tenters is expanded in the conveying direction to stretch (the expansion of the distance between the tenters becomes the stretching ratio). At this time, the distance between the tenters in the width direction (perpendicular to the conveying direction) is arbitrarily set to be close. Preferably, it can be set in a manner closer to free-end stretching with respect to the stretching ratio in the conveying direction. In the case of free-end stretching, the shrinkage rate in the width direction = (1 / stretching ratio) 1 / 2 is calculated.
[0110] The auxiliary stretching in a gas atmosphere can be carried out in one stage or in multiple stages. In the case of multiple-stage stretching, the stretching ratio is the product of the stretching ratios of each stage. The stretching direction in the auxiliary stretching in a gas atmosphere is preferably substantially the same as the stretching direction in the stretching in an aqueous solution.
[0111] The stretching ratio in the auxiliary stretching in a gas atmosphere is preferably 2.0 to 3.5 times. In the case of combining the auxiliary stretching in a gas atmosphere and the stretching in an aqueous solution, the maximum stretching ratio with respect to the original length of the laminate is preferably 5.0 times or more, more preferably 5.5 times or more, and further preferably 6.0 times or more. In this specification, the "maximum stretching ratio" means the stretching ratio just before the laminate breaks. Additionally, when confirming the stretching ratio at which the laminate breaks, the "maximum stretching ratio" means a value 0.2 smaller than this value.
[0112] The stretching temperature in the auxiliary stretching in a gas atmosphere can be set to any appropriate value according to the forming material of the thermoplastic resin substrate, the stretching method, etc. The stretching temperature is preferably above the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably above the glass transition temperature (Tg) of the thermoplastic resin substrate + 10 °C, and particularly preferably above Tg + 15 °C. On the other hand, the upper limit of the stretching temperature is preferably 170 °C. By performing stretching at such a temperature, the rapid progress of the crystallization of the PVA-based resin can be suppressed, and the adverse conditions caused by this crystallization (for example, hindering the orientation of the PVA-based resin layer due to stretching) can be suppressed. The crystallization index of the PVA-based resin after the auxiliary stretching in a gas atmosphere is preferably 1.3 to 1.8, more preferably 1.4 to 1.7. The crystallization index of the PVA-based resin can be measured using a Fourier transform infrared spectrophotometer by the ATR method. Specifically, measurement is performed using polarized light as the measurement light, and the crystallization index is calculated by the following formula using the intensities at 1141 cm -1 and 1440 cm -1 .
[0113] Crystallization index = (I C / I R )
[0114] wherein,
[0115] I C : The intensity at 1141 cm -1 when measuring by making the measurement light incident
[0116] I R : The intensity at 1440 cm -1 when measuring by making the measurement light incident.
[0117] B-3-3. Insolubilization treatment
[0118] As needed, insolubilization treatment is carried out after the auxiliary stretching treatment in a gas atmosphere and before the stretching treatment and dyeing treatment in an aqueous solution. The above insolubilization treatment is typically carried out by immersing the PVA-based resin layer in an aqueous boric acid solution. By carrying out the insolubilization treatment, water resistance can be imparted to the PVA-based resin layer, and the orientation of PVA can be prevented from decreasing when immersed in water. The concentration of the aqueous boric acid solution is preferably 1 part by weight to 4 parts by weight relative to 100 parts by weight of water. The liquid temperature of the insolubilization bath (aqueous boric acid solution) is preferably 20°C to 50°C.
[0119] B-3-4. Dyeing treatment
[0120] The above dyeing treatment is typically carried out by dyeing the PVA-based resin layer with a dichroic substance (typically iodine). Specifically, it is carried out by adsorbing iodine onto the PVA-based resin layer. As this adsorption method, for example, a method of immersing the PVA-based resin layer (laminate) in a dyeing solution containing iodine; a method of applying the dyeing solution to the PVA-based resin layer; a method of spraying the dyeing solution onto the PVA-based resin layer, etc. are exemplified. The method of immersing the laminate in the dyeing solution (dyeing bath) is preferred. This is because iodine can be adsorbed well.
[0121] The above dyeing solution is preferably an aqueous iodine solution. The compounding amount of iodine is preferably 0.05 part by weight to 0.5 part by weight relative to 100 parts by weight of water. In order to increase the solubility of iodine in water, an iodide is preferably compounded in the aqueous iodine solution. As the iodide, for example, potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, titanium iodide, etc. are exemplified. Among these, potassium iodide is preferred. The compounding amount of the iodide is preferably 0.1 part by weight to 10 parts by weight relative to 100 parts by weight of water, and more preferably 0.3 part by weight to 5 parts by weight. In order to suppress the dissolution of the PVA-based resin, the liquid temperature during dyeing with the dyeing solution is preferably 20°C to 50°C. In the case of immersing the PVA-based resin layer in the dyeing solution, in order to ensure the transmittance of the PVA-based resin layer, the immersion time is preferably 5 seconds to 5 minutes, and more preferably 30 seconds to 90 seconds.
[0122] The dyeing conditions (concentration, liquid temperature, immersion time) can be set in such a way that the monomer transmittance of the finally obtained polarizing film is 43.5% or more and the degree of polarization is 99.940% or more. As such dyeing conditions, it is preferred to use an aqueous iodine solution as the dyeing solution and set the content ratio of iodine to potassium iodide in the aqueous iodine solution to 1:5 to 1:20. The content ratio of iodine to potassium iodide in the aqueous iodine solution is preferably 1:5 to 1:10. Thus, a polarizing film having the above-described optical characteristics can be obtained.
[0123] When a dyeing process is continuously carried out after treating a laminate by immersing it in a treatment bath containing boric acid (typically insolubilization treatment), the boric acid concentration in the dyeing bath changes over time by mixing the boric acid contained in the treatment bath. As a result, the dyeability sometimes becomes unstable. To suppress the instability of the dyeability as described above, the upper limit of the boric acid concentration in the dyeing bath is adjusted to preferably 4 parts by weight, more preferably 2 parts by weight, relative to 100 parts by weight of water. On the other hand, the lower limit of the boric acid concentration in the dyeing bath is preferably 0.1 part by weight, more preferably 0.2 part by weight, and further preferably 0.5 part by weight, relative to 100 parts by weight of water. In one embodiment, a dyeing process is carried out using a dyeing bath in which boric acid is pre-formulated. Thereby, the change ratio of the boric acid concentration in the case where the boric acid in the above treatment bath is mixed into the dyeing bath can be reduced. The amount of boric acid pre-formulated in the dyeing bath (i.e., the content of boric acid not from the above treatment bath) is preferably 0.1 part by weight to 2 parts by weight, more preferably 0.5 part by weight to 1.5 part by weight, relative to 100 parts by weight of water.
[0124] B-3-5. Crosslinking treatment
[0125] If necessary, a crosslinking treatment is carried out after the dyeing process and before the stretching treatment in an aqueous solution. The above crosslinking treatment is typically carried out by immersing the PVA-based resin layer in an aqueous boric acid solution. By carrying out the crosslinking treatment, water resistance can be imparted to the PVA-based resin layer, and during the subsequent stretching in an aqueous solution, a decrease in the orientation of PVA when immersed in hot water can be prevented. The concentration of the aqueous boric acid solution is preferably 1 part by weight to 5 parts by weight relative to 100 parts by weight of water. In addition, when the crosslinking treatment is carried out after the above dyeing process, it is preferable to further formulate an iodide. By formulating an iodide, elution of iodine adsorbed on the PVA-based resin layer can be suppressed. The amount of iodide formulated is preferably 1 part by weight to 5 parts by weight relative to 100 parts by weight of water. Specific examples of the iodide are as described above. The liquid temperature of the crosslinking bath (aqueous boric acid solution) is preferably 20°C to 50°C.
[0126] B-3-6. Stretching treatment in an aqueous solution
[0127] The stretching treatment in an aqueous solution is carried out by immersing the laminate in a stretching bath. According to the stretching treatment in an aqueous solution, stretching can be carried out at a temperature lower than the glass transition temperature (typically around 80°C) of the above thermoplastic resin substrate and PVA-based resin layer, and stretching can be carried out at a high magnification while suppressing crystallization of the PVA-based resin layer. As a result, a polarizing film having excellent optical properties can be manufactured.
[0128] Any suitable method can be adopted for the stretching method of the laminate. Specifically, it can be fixed-end stretching or free-end stretching (for example, a method of unidirectionally stretching the laminate by passing it between rollers with different circumferential speeds). Free-end stretching is preferably selected. The stretching of the laminate can be carried out in one stage or in multiple stages. In the case of multiple-stage stretching, the stretching ratio (maximum stretching ratio) of the laminate described later is the product of the stretching ratios of each stage.
[0129] Stretching in an aqueous solution is preferably carried out by immersing the laminate in an aqueous boric acid solution (stretching in an aqueous boric acid solution). By using an aqueous boric acid solution as the stretching bath, rigidity that can withstand the tension applied during stretching and water resistance that does not dissolve in water can be imparted to the PVA-based resin layer. Specifically, boric acid can generate tetrahydroxyborate anions in an aqueous solution and crosslink with the PVA-based resin through hydrogen bonds. As a result, rigidity and water resistance can be imparted to the PVA-based resin layer, stretching can be carried out well, and a polarizing film with excellent optical properties can be manufactured.
[0130] The above-mentioned aqueous boric acid solution is preferably obtained by dissolving boric acid and / or borate in water as a solvent. The boric acid concentration is preferably 1 part by weight to 10 parts by weight, more preferably 2.5 parts by weight to 6 parts by weight, and particularly preferably 3 parts by weight to 5 parts by weight relative to 100 parts by weight of water. By setting the boric acid concentration to 1 part by weight or more, the dissolution of the PVA-based resin layer can be effectively suppressed, and a polarizing film with higher properties can be manufactured. It should be noted that an aqueous solution obtained by dissolving boron compounds such as borax other than boric acid or borate, glyoxal, glutaraldehyde, etc. in a solvent can also be used.
[0131] It is preferable to incorporate an iodide in the above-mentioned stretching bath (aqueous boric acid solution). By incorporating an iodide, the elution of iodine adsorbed on the PVA-based resin layer can be suppressed. Specific examples of the iodide are as described above. The concentration of the iodide is preferably 0.05 part by weight to 15 parts by weight, more preferably 0.5 part by weight to 8 parts by weight relative to 100 parts by weight of water.
[0132] The stretching temperature (liquid temperature of the stretching bath) is preferably 40°C to 85°C, more preferably 60°C to 75°C. If the temperature is such, the dissolution of the PVA-based resin layer can be suppressed, and stretching can be carried out at a high ratio. Specifically, as described above, considering the relationship with the PVA-based resin layer, the glass transition temperature (Tg) of the thermoplastic resin substrate is preferably 60°C or higher. In this case, when the stretching temperature is lower than 40°C, there is a concern that even considering the plasticization of the thermoplastic resin substrate by water, stretching cannot be carried out well. On the other hand, the higher the temperature of the stretching bath, the higher the solubility of the PVA-based resin layer, and there is a concern that excellent optical properties cannot be obtained. The immersion time of the laminate in the stretching bath is preferably 15 seconds to 5 minutes.
[0133] The draw ratio in the draw in an aqueous solution is preferably 1.5 times or more, more preferably 3.0 times or more. The total draw ratio of the laminate with respect to the original length of the laminate is preferably 5.0 times or more, and further preferably 5.5 times or more. By achieving such a high draw ratio, a polarizing film with very excellent optical properties can be manufactured. Such a high draw ratio can be achieved by adopting a draw method in an aqueous solution (draw in a boric acid aqueous solution).
[0134] B-3-7. Drying shrinkage treatment
[0135] The above drying shrinkage treatment can be carried out by zone heating by heating the entire area, or can be carried out by heating the transport rollers (using a so-called heating roller) (heating roller drying method). It is preferable to use both. By drying using a heating roller, the heating curl of the laminate can be efficiently suppressed, and thus a polarizing film with excellent appearance can be manufactured. Specifically, by drying the laminate in a state along the heating roller, the crystallization of the above thermoplastic resin substrate can be efficiently promoted, and the crystallinity can be increased. Even at a relatively low drying temperature, the crystallinity of the thermoplastic resin substrate can be increased well. As a result, the rigidity of the thermoplastic resin substrate increases, and it becomes a state that can withstand the shrinkage of the PVA-based resin layer caused by drying, and the curl can be suppressed. In addition, by using a heating roller, the laminate can be dried while being kept in a flat state. Therefore, not only can the curl be suppressed, but also the generation of wrinkles can be suppressed. At this time, the laminate is shrunk in the width direction by the drying shrinkage treatment, and thereby the optical properties can be improved. This is because the orientation of PVA and the PVA / iodine complex can be effectively improved. The shrinkage rate of the laminate in the width direction by the drying shrinkage treatment is preferably 1% to 10%, more preferably 2% to 8%, and particularly preferably 4% to 6%. By using a heating roller, the laminate can be transported while being continuously shrunk in the width direction, and high productivity can be achieved.
[0136] Figure 4 It is a schematic diagram showing an example of the drying shrinkage treatment. In the drying shrinkage treatment, the laminate 200 is dried while being transported by the transport rollers R1 to R6 and the guide rollers G1 to G4 heated to a given temperature. In the illustrated example, the transport rollers R1 to R6 are arranged in such a manner that the surfaces of the PVA resin layer and the thermoplastic resin substrate are alternately and continuously heated, but the transport rollers R1 to R6 can also be arranged, for example, in such a manner that only one surface (for example, the thermoplastic resin substrate surface) of the laminate 200 is continuously heated.
[0137] By adjusting the heating temperature of the conveying rollers (the temperature of the heating rollers), the number of heating rollers, the contact time with the heating rollers, etc., the drying conditions can be controlled. The temperature of the heating rollers is preferably 60°C to 120°C, more preferably 65°C to 100°C, and particularly preferably 70°C to 80°C. The crystallinity of the thermoplastic resin can be increased well, curling can be suppressed well, and an optical laminate with extremely excellent durability can be manufactured. It should be noted that the temperature of the heating rollers can be measured by a contact thermometer. In the illustrated example, 6 conveying rollers are provided, but there is no particular limitation as long as there are multiple conveying rollers. Usually, 2 to 40 conveying rollers are provided, and preferably 4 to 30 conveying rollers are provided. The contact time (total contact time) between the laminate and the heating rollers is preferably 1 second to 300 seconds, more preferably 1 to 20 seconds, and further preferably 1 to 10 seconds.
[0138] The heating rollers can be provided in a heating furnace (such as an oven), or can be provided in a normal manufacturing line (at room temperature environment). It is preferably provided in a heating furnace equipped with a blowing mechanism. By combining the drying using the heating rollers and hot air drying, a sharp temperature change between the heating rollers can be suppressed, and the shrinkage in the width direction can be easily controlled. The temperature of the hot air drying is preferably 30°C to 100°C. In addition, the hot air drying time is preferably 1 second to 300 seconds. The wind speed of the hot air is preferably about 10 m / s to 30 m / s. It should be noted that this wind speed is the wind speed inside the heating furnace and can be measured by a mini vane type digital anemometer.
[0139] B-3-8. Other Treatments
[0140] It is preferable to perform a cleaning treatment after the stretching treatment in an aqueous solution and before the drying shrinkage treatment. The above-mentioned cleaning treatment is typically performed by immersing the PVA-based resin layer in an aqueous potassium iodide solution.
[0141] C. First Phase Difference Layer
[0142] As described above, the first phase difference layer 20 is an alignment fixing layer of a liquid crystal compound. By using a liquid crystal compound, the difference between nx and ny of the obtained phase difference layer can be greatly increased compared with a non-liquid crystal material. Therefore, the thickness of the phase difference layer for obtaining a desired in-plane phase difference can be greatly reduced. As a result, further thinning and lightening of the polarizing plate with a phase difference layer can be achieved. In this specification, the "alignment fixing layer" means a layer in which a liquid crystal compound is aligned in a given direction in the layer and its alignment state is fixed. It should be noted that the "alignment fixing layer" is a concept including an alignment cured layer obtained by curing a liquid crystal monomer, as described later. In this embodiment, typically, rod-shaped liquid crystal compounds are aligned (homogeneously aligned) in a state of being juxtaposed along the slow axis direction of the phase difference layer.
[0143] As liquid crystal compounds, for example, liquid crystal compounds having a nematic liquid crystal phase (nematic liquid crystals) can be cited. As such liquid crystal compounds, for example, liquid crystal polymers and liquid crystal monomers can be used. The mechanism for the manifestation of the liquid crystallinity of the liquid crystal compound can be lyotropic or thermotropic. The liquid crystal polymer and the liquid crystal monomer can be used alone or in combination.
[0144] When the liquid crystal compound is a liquid crystal monomer, it is preferable that the liquid crystal monomer is a polymerizable monomer and a crosslinkable monomer. This is because by polymerizing or crosslinking (i.e., curing) the liquid crystal monomer, the orientation state of the liquid crystal monomer can be fixed. After the liquid crystal monomer is oriented, for example, if the liquid crystal monomers are polymerized or crosslinked with each other, the above-mentioned orientation state can be fixed thereby. Here, a polymer is formed by polymerization and a three-dimensional network structure is formed by crosslinking, but they are non-liquid crystalline. Therefore, the formed first retardation layer does not undergo, for example, a transition to a liquid crystal phase, a glass phase, or a crystal phase due to a temperature change peculiar to the liquid crystalline compound. As a result, the first retardation layer becomes a retardation layer that is not affected by temperature changes and has extremely excellent stability.
[0145] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on its type. Specifically, this temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.
[0146] As the above-mentioned liquid crystal monomer, any suitable liquid crystal monomer can be employed. For example, polymerizable mesogenic compounds described in JP-T 2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445, etc. can be used. As specific examples of such polymerizable mesogenic compounds, for example, LC242, a product name of BASF Corporation, E7, a product name of Merck KGaA, and LC-Sillicon-CC3767, a product name of Wacker-Chemie GmbH can be cited. As the liquid crystal monomer, a nematic liquid crystal monomer is preferably used, for example.
[0147] The alignment fixing layer of the liquid crystal compound can be formed by the following method: performing an alignment treatment on the surface of a given substrate, coating a coating liquid containing the liquid crystal compound on the surface, aligning the liquid crystal compound in a direction corresponding to the above alignment treatment, and fixing the alignment state. In one embodiment, the substrate is any suitable resin film, and the alignment fixing layer formed on the substrate can be transferred to the surface of the polarizing plate 10. In another embodiment, the substrate can be the second protective layer 13. In this case, the transfer process is omitted, and lamination can be continuously performed by roll-to-roll after forming the alignment fixing layer (the first retardation layer), so that productivity can be further improved.
[0148] As the above alignment treatment, any suitable alignment treatment can be adopted. Specifically, examples include: mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment. As specific examples of the mechanical alignment treatment, friction treatment and stretching treatment can be cited. As specific examples of the physical alignment treatment, magnetic field alignment treatment and electric field alignment treatment can be cited. As specific examples of the chemical alignment treatment, inclined evaporation coating method and photo-alignment treatment can be cited. The treatment conditions of various alignment treatments can be any suitable conditions according to the purpose.
[0149] The alignment of the liquid crystal compound can be carried out as follows: treating at a temperature at which the liquid crystal phase is exhibited according to the type of the liquid crystal compound. By performing such temperature treatment, the liquid crystal compound becomes a liquid crystal state, and the liquid crystal compound aligns in accordance with the alignment treatment direction of the substrate surface.
[0150] In one embodiment, the fixation of the alignment state is carried out by cooling the aligned liquid crystal compound as described above. In the case where the liquid crystal compound is a polymerizable monomer or a crosslinkable monomer, the fixation of the alignment state can be carried out by performing a polymerization treatment or a crosslinking treatment on the aligned liquid crystal compound as described above.
[0151] Specific examples of the liquid crystal compound and details of the method for forming the alignment fixing layer are described in Japanese Patent Laid-Open No. 2006-163343. The description of this publication is incorporated herein by reference.
[0152] As other examples of the alignment fixing layer, the alignment modes of discotic liquid crystal compounds in any state among vertical alignment, hybrid alignment, and tilted alignment can be cited. For discotic liquid crystal compounds, typically, the disc plane of the discotic liquid crystal compound is aligned substantially perpendicular to the film plane of the first retardation layer. Substantially perpendicular for the discotic liquid crystal compound means that the average value of the angle formed by the film plane and the disc plane of the discotic liquid crystal compound is preferably 70° to 90°, more preferably 80° to 90°, and still more preferably 85° to 90°. Discotic liquid crystal compounds generally refer to liquid crystal compounds having a disc-shaped molecular structure, where the disc-shaped molecular structure is formed by arranging a cyclic parent nucleus such as benzene, 1,3,5-triazine, calixarene, etc. at the center of the molecule, and radially substituting straight-chain alkyl groups, alkoxy groups, substituted benzoyloxy groups, etc. as its side chains. As representative examples of discotic liquid crystals, there can be cited benzene derivatives, triphenylene derivatives, truxene derivatives, phthalocyanine derivatives described in the research report by C. Destrade et al., Mol. Cryst. Liq. Cryst. Vol. 71, p. 111 (1981); cyclohexane derivatives described in the research report by B. Kohne et al., Angew. Chem. Vol. 96, p. 70 (1984); and macrocycles such as azacrown ethers and phenylacetylenes described in the research report by J. M. Lehn et al., J. Chem. Soc. Chem. Commun., p. 1794 (1985), and the research report by J. Zhang et al., J. Am. Chem. Soc. Vol. 116, p. 2655 (1994). As other specific examples of discotic liquid crystal compounds, there can be cited, for example, the compounds described in Japanese Patent Application Laid-Open No. 2006-133652, Japanese Patent Application Laid-Open No. 2007-108732, and Japanese Patent Application Laid-Open No. 2010-244038. The descriptions in the above-mentioned literature and gazettes are hereby incorporated by reference into this specification.
[0153] In one embodiment, as shown in Figure 1 and Figure 2 , the first retardation layer 20 is a single layer of the alignment fixing layer of the liquid crystal compound. When the first retardation layer 20 is composed of a single layer of the alignment fixing layer of the liquid crystal compound, its thickness is preferably 0.5 μm to 7 μm, more preferably 1 μm to 5 μm. By using the liquid crystal compound, an in-plane retardation equivalent to that of a resin film can be achieved with a thickness significantly thinner than that of the resin film.
[0154] Typically, the refractive index characteristics of the first retardation layer show a relationship of nx > ny = nz. The first retardation layer is typically provided to impart an antireflection property to the polarizing plate. In the case where the first retardation layer is a single layer of an alignment-fixed layer, it can function as a λ / 4 wave plate. In this case, the in-plane retardation Re(550) of the first retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and still more preferably 130 nm to 160 nm. It should be noted that here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within the range that does not impair the effects of the present invention, it may sometimes be ny > nz or ny < nz.
[0155] The Nz coefficient of the first retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3. By satisfying such a relationship, when the resulting polarizing plate with a retardation layer is used in an image display device, a very excellent reflected hue can be achieved.
[0156] The first retardation layer may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases in accordance with the wavelength of the measurement light, a positive wavelength dispersion characteristic in which the retardation value decreases in accordance with the wavelength of the measurement light, or a flat wavelength dispersion characteristic in which the retardation value hardly changes with the wavelength of the measurement light. In one embodiment, the first retardation layer exhibits an inverse dispersion wavelength characteristic. In this case, Re(450) / Re(550) of the retardation layer is preferably 0.8 or more and less than 1, more preferably 0.8 or more and 0.95 or less. If configured in this way, a very excellent antireflection property can be achieved.
[0157] The angle θ formed by the slow axis of the first retardation layer 20 and the absorption axis of the polarizing film 11 is preferably 40° to 50°, more preferably 42° to 48°, and still more preferably about 45°. When the angle θ is in such a range, as described above, by setting the first retardation layer as a λ / 4 wave plate, a polarizing plate with a retardation layer having very excellent circular polarization characteristics (and as a result, very excellent antireflection characteristics) can be obtained.
[0158] In another embodiment, the first retardation layer 20 is as Figure 3As shown, a stacked structure may have a first alignment fixing layer 21 and a second alignment fixing layer 22. In this case, either the first alignment fixing layer 21 or the second alignment fixing layer 22 can function as a λ / 4 wave plate, and the other can function as a λ / 2 wave plate. Therefore, the thicknesses of the first alignment fixing layer 21 and the second alignment fixing layer 22 can be adjusted in such a way as to obtain the desired in-plane phase difference of a λ / 4 wave plate or a λ / 2 wave plate. For example, when the first alignment fixing layer 21 functions as a λ / 2 wave plate and the second alignment fixing layer 22 functions as a λ / 4 wave plate, the thickness of the first alignment fixing layer 21 is, for example, 2.0 μm to 3.0 μm, and the thickness of the second alignment fixing layer 22 is, for example, 1.0 μm to 2.0 μm. In this case, the in-plane phase difference Re(550) of the first alignment fixing layer is preferably 200 nm to 300 nm, more preferably 230 nm to 290 nm, and further preferably 250 nm to 280 nm. Regarding a single-layer alignment fixing layer, the in-plane phase difference Re(550) of the second alignment fixing layer is as described above. The angle formed by the slow axis of the first alignment fixing layer and the absorption axis of the polarizing film is preferably 10° to 20°, more preferably 12° to 18°, and further preferably about 15°. The angle formed by the slow axis of the second alignment fixing layer and the absorption axis of the polarizing film is preferably 70° to 80°, more preferably 72° to 78°, and further preferably about 75°. If it is such a configuration, characteristics close to ideal inverse wavelength dispersion characteristics can be obtained, and as a result, very excellent antireflection characteristics can be achieved. Regarding the liquid crystal compound constituting the first alignment fixing layer and the second alignment fixing layer, the formation method of the first alignment fixing layer and the second alignment fixing layer, optical characteristics, etc., for a single-layer alignment fixing layer are as described above.
[0159] D. Second phase difference layer
[0160] As described above, the second phase difference layer can be a so-called negative C-plate in which the refractive index characteristics show a relationship of nz > nx = ny. By using a negative C-plate as the second phase difference layer, reflection in the tilt direction can be well prevented, and wide viewing angleization of the antireflection function can be achieved. In this case, the phase difference Rth(550) in the thickness direction of the second phase difference layer is preferably -50 nm to -300 nm, more preferably -70 nm to -250 nm, further preferably -90 nm to -200 nm, and particularly preferably -100 nm to -180 nm. Here, "nx = ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane phase difference Re(550) of the second phase difference layer can be less than 10 nm.
[0161] The second retardation layer having a refractive index characteristic of nz > nx = ny can be formed of any suitable material. The second retardation layer is preferably formed of a film containing a liquid crystal material fixed in a homeotropic alignment orientation. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned can be a liquid crystal monomer or a liquid crystal polymer. As specific examples of the liquid crystal compound and the method for forming the retardation layer, the liquid crystal compounds and the method for forming the retardation layer described in
[0020] to
[0028] of Japanese Patent Laid-Open No. 2002-333642 can be cited. In this case, the thickness of the second retardation layer is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and still more preferably 0.5 μm to 5 μm.
[0162] E. Conductive layer or isotropic substrate with a conductive layer
[0163] The conductive layer can be formed by forming a metal oxide film on any suitable substrate by any suitable film-forming method (for example, vacuum evaporation method, sputtering method, CVD method, ion plating method, spraying method, etc.). As the metal oxide, for example, indium oxide, tin oxide, zinc oxide, indium-tin composite oxide, tin-antimony composite oxide, zinc-aluminum composite oxide, indium-zinc composite oxide can be cited. Among them, indium-tin composite oxide (ITO) is preferred.
[0164] When the conductive layer contains a metal oxide, the thickness of the conductive layer is preferably 50 nm or less, more preferably 35 nm or less. The lower limit of the thickness of the conductive layer is preferably 10 nm.
[0165] The conductive layer can be transferred from the above substrate to the first retardation layer (or the second retardation layer when there is a second retardation layer), and the conductive layer can be used alone as a constituent layer of the polarizer with a retardation layer, or it can be made into a laminate with the substrate (substrate with a conductive layer) and laminated on the first retardation layer (or the second retardation layer when there is a second retardation layer). It is preferred that the above substrate is optically isotropic. Therefore, the conductive layer can be used as an isotropic substrate with a conductive layer for a polarizer with a retardation layer.
[0166] As the optically isotropic substrate (isotropic substrate), any suitable isotropic substrate can be used. As the material constituting the isotropic substrate, for example, materials mainly composed of resins without a conjugated system such as norbornene resins and olefin resins; materials having a cyclic structure such as a lactone ring and a glutarimide ring in the main chain of an acrylic resin, etc. can be cited. If such materials are used, when forming the isotropic substrate, the retardation exhibited due to the orientation of the molecular chain can be suppressed to a relatively low level. The thickness of the isotropic substrate is preferably 50 μm or less, more preferably 35 μm or less. The lower limit of the thickness of the isotropic substrate is, for example, 20 μm.
[0167] The above-mentioned conductive layer and / or the conductive layer of the isotropic substrate with a conductive layer can be patterned as needed. Through patterning, a conduction part and an insulating part can be formed. As a result, an electrode can be formed. The electrode can function as a touch sensor electrode for sensing contact with the touch panel. As a patterning method, any appropriate method can be adopted. As a specific example of the patterning method, a wet etching method and a screen printing method can be cited.
[0168] F. Image display device
[0169] The polarizing plate with a retardation layer described in the above items A to E can be applied to an image display device. Therefore, the present invention includes an image display device using such a polarizing plate with a retardation layer. As a representative example of the image display device, a liquid crystal display device and an electroluminescence (EL) display device (for example, an organic EL display device and an inorganic EL display device) can be cited. The image display device according to an embodiment of the present invention includes, on its visible side, the polarizing plate with a retardation layer described in the above items A to E. The polarizing plate with a retardation layer is laminated in such a manner that the retardation layer faces the image display unit (for example, a liquid crystal unit, an organic EL unit, an inorganic EL unit) side (the polarizing film faces the visible side). In one embodiment, the image display device may have a curved shape (substantially a curved display screen) and / or be bendable or foldable. In such an image display device, the effects of the polarizing plate with a retardation layer of the present invention become remarkable.
[0170] Examples
[0171] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. The measurement methods for each property are as described below. It should be noted that unless otherwise specified, "parts" and "%" in the examples and comparative examples are based on weight.
[0172] (1) Thickness
[0173] For a thickness of 10 μm or less, it is measured using an interference film thickness meter (manufactured by Otsuka Electronics Co., Ltd., product name "MCPD-3000"). For a thickness greater than 10 μm, it is measured using a digital micrometer (manufactured by Anritsu Corporation, product name "KC-351C").
[0174] (2) Monomer transmittance and degree of polarization
[0175] For the laminate (polarizer) of a polarizing film / protective layer used in the examples and comparative examples, the monomer transmittance Ts, parallel transmittance Tp, and orthogonal transmittance Tc measured using an ultraviolet-visible spectrophotometer (V-7100 manufactured by JASCO Corporation) were used as Ts, Tp, and Tc of the polarizing film, respectively. These Ts, Tp, and Tc are Y values obtained by measuring through a 2-degree field of view (C light source) in accordance with JIS Z8701 and performing visibility correction. It should be noted that the refractive index of the protective layer is 1.50, and the refractive index of the surface of the polarizing film on the side opposite to the protective layer is 1.53.
[0176] Based on the obtained Tp and Tc, the degree of polarization P was calculated using the following formula.
[0177] Degree of polarization P (%) = {(Tp - Tc) / (Tp + Tc)} 1 / 2 × 100
[0178] It should be noted that a spectrophotometer such as LPF-200 manufactured by Otsuka Electronics Co., Ltd. can be used for equivalent measurements. As an example, for Samples 1 to 3 of polarizers having the same configuration as the following examples, the monomer transmittance Ts and the degree of polarization P were obtained by measurements using V-7100 and LPF-200, and their measured values are shown in Table 1. As shown in Table 1, it can be seen that the difference between the measured values of the monomer transmittance of V-7100 and the measured values of the monomer transmittance of LPF-200 is 0.1% or less, and equivalent measurement results are obtained regardless of which spectrophotometer is used.
[0179]
[0180] It should be noted that, for example, when a polarizer that has been subjected to an anti-glare (AG) surface treatment and has an adhesive with diffusion properties is used as the measurement object, different measurement results may be obtained depending on the spectrophotometer. In this case, numerical conversion is performed based on the measured values when the same polarizer is measured using each spectrophotometer, thereby compensating for the difference in the measured values depending on the spectrophotometer.
[0181] (3) Deviation in optical properties of a strip-shaped polarizing film
[0182] From the polarizers used in the examples and comparative examples, measurement samples were cut out at five positions at equal intervals along the width direction, and the monomer transmittance of the central part of each of the five measurement samples was measured in the same manner as in (2) above. Subsequently, the difference between the maximum value and the minimum value among the monomer transmittances measured at each measurement position was calculated, and this value was defined as the deviation in the optical properties of the strip-shaped polarizing film.
[0183] (4) Deviation in optical properties of a single-piece polarizing film
[0184] From the polarizing plates used in the examples and comparative examples, a 100 mm × 100 mm measurement sample was cut out, and the deviation of the optical properties of a single-sheet polarizing plate (50 cm 2 ) was determined. Specifically, in the same manner as in (2) above, the monomer transmittance at a total of five positions, namely, positions near about 1.5 cm to 2.0 cm inward from the midpoints of each of the four sides of the measurement sample and the central portion, was measured. Next, the difference between the maximum value and the minimum value among the monomer transmittances measured at each measurement position was calculated, and this value was set as the deviation of the optical properties of the single-sheet polarizing film.
[0185] (5) Warpage
[0186] A polarizing plate with a retardation layer obtained in the examples and comparative examples was cut out to a size of 110 mm × 60 mm. At this time, it was cut out such that the absorption axis direction of the polarizing film became the long side direction. The cut polarizing plate with a retardation layer was adhered to a glass plate having a size of 120 mm × 70 mm and a thickness of 0.2 mm using an adhesive to obtain a test sample. The test sample was placed in a heating oven maintained at 85°C for 24 hours, and the amount of warpage after removal was measured. When the test sample was placed statically on a plane with the glass plate facing down, the height of the highest part from this plane was taken as the amount of warpage.
[0187] (6) Unit weight
[0188] A polarizing plate with a retardation layer obtained in the examples and comparative examples was cut out to a given size, and the weight (mg) was divided by the area (cm 2 ) to calculate the weight per unit area (unit weight) of the polarizing plate with a retardation layer.
[0189] (7) Flex resistance
[0190] A polarizing plate with a retardation layer obtained in the examples and comparative examples was cut out to a size of 50 mm × 100 mm. At this time, it was cut out such that the absorption axis direction of the polarizing film became the short side direction. Using a flex resistance testing machine (manufactured by YUASA Corporation, CL09 type-D01) equipped with a constant temperature and humidity chamber, the cut polarizing plate with a retardation layer was subjected to a bending test under the conditions of 20°C and 50% RH. Specifically, the polarizing plate with a retardation layer was repeatedly bent in a direction parallel to the absorption axis direction with the retardation layer side facing outward, and the number of bends until cracks, peeling, film breakage, etc. that showed defects occurred was measured, and evaluation was carried out according to the following criteria (bending diameter: 2 mmφ).
[0191] <Evaluation criteria>
[0192] Less than 10,000 times: Defective
[0193] 10,000 times or more and less than 30,000 times: Good
[0194] More than 30,000 times: excellent
[0195] [Example 1]
[0196] 1. Fabrication of Polarizing Film
[0197] As the thermoplastic resin substrate, an amorphous isophthalic acid copolyethylene terephthalate film (thickness: 100 μm) in the form of a long strip with a water absorption rate of 0.75% and a Tg of about 75°C was used. Corona treatment was performed on one side of the resin substrate.
[0198] In 100 parts by weight of a PVA-based resin obtained by mixing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name “GOHSEFIMER Z410”) in a ratio of 9:1, 13 parts by weight of potassium iodide was added, and the resulting mixture was dissolved in water to prepare a PVA aqueous solution (coating solution).
[0199] The above-mentioned PVA aqueous solution was coated on the corona-treated surface of the resin substrate and dried at 60°C, thereby forming a PVA-based resin layer with a thickness of 13 μm to fabricate a laminate.
[0200] In an oven at 130°C, between rollers with different circumferential speeds, the resulting laminate was unidirectionally stretched longitudinally (in the length direction) to 2.4 times at the free end (auxiliary stretching treatment in a gas atmosphere).
[0201] Next, the laminate was immersed in an insolubilization bath at a liquid temperature of 40°C (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) for 30 seconds (insolubilization treatment).
[0202] Next, in a dyeing bath at a liquid temperature of 30°C (an iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water), the laminate was immersed for 60 seconds while adjusting the concentration so that the monomer transmittance (Ts) of the finally obtained polarizing film became 43.5% or more (dyeing treatment).
[0203] Next, the laminate was immersed in a crosslinking bath at a liquid temperature of 40°C (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with 100 parts by weight of water) for 30 seconds (crosslinking treatment).
[0204] Then, while immersing the laminate in a boric acid aqueous solution at a liquid temperature of 70°C (boric acid concentration 4.0% by weight), between rollers with different circumferential speeds, unidirectional stretching was performed so that the total stretching ratio in the longitudinal direction (length direction) became 5.5 times (stretching treatment in an aqueous solution).
[0205] Then, the laminate was immersed in a cleaning bath at a liquid temperature of 20°C (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) (cleaning treatment).
[0206] Then, while drying in an oven maintained at 90°C, it was brought into contact with a SUS heating roller having a surface temperature maintained at 75°C for about 2 seconds (dry shrinkage treatment). The shrinkage rate of the laminate in the width direction was 2% by the dry shrinkage treatment.
[0207] In this way, a polarizing film with a thickness of 5 μm was formed on the resin substrate.
[0208] 2. Fabrication of Polarizer
[0209] On the surface of the above-obtained polarizing film (the side opposite to the resin substrate), an acrylic film (surface refractive index 1.50, 40 μm) was adhered as a protective layer through an ultraviolet-curable adhesive. Specifically, it was coated so that the total thickness of the curable adhesive became 1.0 μm, and lamination was performed using a roller machine. Then, UV light was irradiated from the protective layer side to cure the adhesive. Next, after cutting both ends, the resin substrate was peeled off to obtain a strip-shaped polarizer (width: 1300 mm) having a structure of protective layer / polarizing film. The monomer transmittance of the polarizer (substantially a polarizing film) was 43.76% and the degree of polarization was 99.980%. In addition, the deviation of the optical properties of the strip-shaped polarizing film was 0.14%, and the deviation of the optical properties of the single-sheet polarizing film was 0.06%.
[0210] 3. Fabrication of the First Alignment Fixing Layer and the Second Alignment Fixing Layer Constituting the Phase Difference Layer
[0211] 10 g of a polymerizable liquid crystal showing a nematic liquid crystal phase (manufactured by BASF: trade name "Paliocolor LC242", represented by the following formula) and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: trade name "IRGACURE907") were dissolved in 40 g of toluene to prepare a liquid crystal composition (coating solution).
[0212] [Chemical formula 1]
[0213]
[0214] The surface of a polyethylene terephthalate (PET) film (thickness 38 μm) was rubbed with a rubbing cloth to perform an alignment treatment. When bonded to a polarizer, the direction of the alignment treatment was 15° from the absorption axis of the polarizing film as viewed from the visible side. The above liquid crystal coating solution was applied to the surface of this alignment treatment using a bar coater and dried by heating at 90 °C for 2 minutes, thereby aligning the liquid crystal compound. Using a metal halide lamp, light of 1 mJ / cm 2 was irradiated onto the liquid crystal layer thus formed to cure the liquid crystal layer. Thereby, a liquid crystal alignment fixing layer A was formed on the PET film. The thickness of the liquid crystal alignment fixing layer A was 2.5 μm, and the in-plane retardation Re(550) was 270 nm. In addition, the liquid crystal alignment fixing layer A had a refractive index distribution of nx > ny = nz.
[0215] The coating thickness was changed, and the alignment treatment direction was set to 75° from the absorption axis of the polarizing film as viewed from the visible side. Except for this, a liquid crystal alignment fixing layer B was formed on the PET film in the same manner as above. The thickness of the liquid crystal alignment fixing layer B was 1.5 μm, and the in-plane retardation Re(550) was 140 nm. In addition, the liquid crystal alignment fixing layer B had a refractive index distribution of nx > ny = nz.
[0216] 4. Fabrication of a Polarizer with a Retardation Layer
[0217] The liquid crystal alignment fixing layer A and the liquid crystal alignment fixing layer B obtained in the above 3. were sequentially transferred onto the surface of the polarizing film of the polarizer obtained in the above 2. At this time, transfer (bonding) was performed such that the angle formed by the absorption axis of the polarizing film and the slow axis of the alignment fixing layer A was 15°, and the angle formed by the absorption axis of the polarizing film and the slow axis of the alignment fixing layer B was 75°. It should be noted that each transfer (bonding) was performed using the ultraviolet curable adhesive (thickness 1.0 μm) used in the above 2. In this way, a polarizer with a retardation layer having a structure of protective layer / adhesive layer / polarizing film / adhesive layer / retardation layer (first alignment fixing layer / adhesive layer / second alignment fixing layer) was obtained. The total thickness of the obtained polarizer with a retardation layer was 52 μm. The obtained polarizer with a retardation layer was subjected to the evaluation in the above (5) to (7). The warpage amount was 1.8 mm.
[0218] [Example 2]
[0219] An acrylic film with a thickness of 20 μm was used as the protective layer, and except for this, a polarizer with a retardation layer was produced in the same manner as in Example 1. The total thickness of the obtained polarizer with a retardation layer was 32 μm. The obtained polarizer with a retardation layer was subjected to the same evaluation as in Example 1. The warpage amount was 1.5 mm.
[0220] [Example 3]
[0221] A cellulose triacetate (TAC) film with a thickness of 25 μm was used as the protective layer. Except for this, a polarizing plate with a retardation layer was produced in the same manner as in Example 1. The total thickness of the obtained polarizing plate with a retardation layer was 37 μm. The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The amount of warpage was 1.3 mm.
[0222] [Comparative Example 1]
[0223] 1. Production of a polarizer
[0224] A polyvinyl alcohol resin film with an average degree of polymerization of 2400, a saponification degree of 99.9 mol%, and a thickness of 30 μm was prepared. While immersing the polyvinyl alcohol film in a swelling bath (water bath) at 20 °C for 30 seconds to swell it, it was stretched 2.4 times in the transport direction between rolls with different circumferential speed ratios (swelling process). Then, in a dyeing bath at 30 °C (an aqueous solution with an iodine concentration of 0.03 wt% and a potassium iodide concentration of 0.3 wt%), while immersing and dyeing it so that the monomer transmittance after the final stretching became the desired value, it was stretched 3.7 times in the transport direction based on the original polyvinyl alcohol film (the polyvinyl alcohol film that was not stretched at all in the transport direction) (dyeing process). The immersion time at this time was about 60 seconds. Next, while immersing the dyed polyvinyl alcohol film in a crosslinking bath at 40 °C (an aqueous solution with a boric acid concentration of 3.0 wt% and a potassium iodide concentration of 3.0 wt%), it was stretched 4.2 times in the transport direction based on the original polyvinyl alcohol film (crosslinking process). Further, the obtained polyvinyl alcohol film was immersed in a stretching bath at 64 °C (an aqueous solution with a boric acid concentration of 4.0 wt% and a potassium iodide concentration of 5.0 wt%) for 50 seconds, and stretched 6.0 times in the transport direction based on the original polyvinyl alcohol film (stretching process), and then immersed in a cleaning bath at 20 °C (an aqueous solution with a potassium iodide concentration of 3.0 wt%) for 5 seconds (cleaning process). The cleaned polyvinyl alcohol film was dried at 30 °C for 2 minutes to produce a polarizer (thickness 12 μm).
[0225] 2. Production of a polarizing plate
[0226] As the adhesive, an aqueous solution containing polyvinyl alcohol resin having acetoacetyl groups (average degree of polymerization: 1200, saponification degree: 98.5 mol%, acetoacetylation rate: 5 mol%) and hydroxymethyl melamine in a weight ratio of 3:1 was used. Using this adhesive and a roll laminator, a hard coat-containing triacetyl cellulose (TAC) film with a thickness of 25 μm was laminated on one side of the polarizer obtained above, and a TAC film with a thickness of 25 μm was laminated on the other side of the polarizer. Then, it was heated and dried in an oven (temperature: 60 °C, time: 5 minutes) to fabricate a polarizing plate having a structure of protective layer 1 (thickness 25 μm) / adhesive layer / polarizer / adhesive layer / protective layer 2 (thickness 25 μm).
[0227] 3. Fabrication of a polarizing plate with a retardation layer
[0228] On the surface of the protective layer 2 of the polarizing plate obtained in 2. above, a liquid crystal alignment fixing layer A and a liquid crystal alignment fixing layer B were sequentially transferred in the same manner as in Example 1 to fabricate a polarizing plate with a retardation layer having a structure of protective layer 1 / adhesive layer / polarizer / adhesive layer / protective layer 2 / adhesive layer / retardation layer (first alignment fixing layer / adhesive layer / second alignment fixing layer). The total thickness of the obtained polarizing plate with a retardation layer was 68 μm. The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The warpage amount was 4.2 mm.
[0229] [Comparative Example 2]
[0230] Potassium iodide was not added to the PVA aqueous solution (coating solution), the drawing ratio in the auxiliary drawing treatment in a gas atmosphere was set to 1.8 times, and a heating roll was not used in the drying shrinkage treatment. Otherwise, a polarizing film and a polarizing plate were fabricated in the same manner as in Example 1. The monomer transmittance of the polarizing plate (substantially a polarizing film) was 43.13%, and the degree of polarization was 99.881%. Except for using this polarizing plate, a polarizing plate with a retardation layer was fabricated in the same manner as in Example 1.
[0231] [Comparative Example 3]
[0232] 1. Fabrication of a polarizing plate
[0233] A TAC film with a thickness of 25 μm was used as the protective layer, and otherwise, a strip-shaped polarizing plate (width: 1300 mm) having a structure of protective layer / polarizing film was obtained in the same manner as in Example 1.
[0234] 2. Fabrication of a retardation film constituting a retardation layer
[0235] 2-1. Polymerization of a polyester carbonate resin
[0236] Polymerization was carried out using a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and a reflux condenser controlled at 100 °C. 29.60 parts by mass (0.046 mol) of bis[9-(2-phenoxycarbonylethyl)fluorene-9-yl]methane, 29.21 parts by mass (0.200 mol) of isosorbide (ISB), 42.28 parts by mass (0.139 mol) of spirodiol (SPG), 63.77 parts by mass (0.298 mol) of diphenyl carbonate (DPC), and 1.19×10 -2 parts by mass (6.78×10 -5 mol) of calcium acetate monohydrate as a catalyst. After evacuating and replacing the inside of the reactor with nitrogen, it was heated with a heat medium, and stirring was started when the internal temperature reached 100 °C. Forty minutes after the start of temperature increase, the internal temperature was raised to 220 °C, and while controlling and maintaining this temperature, decompression was started, and 13.3 kPa was reached 90 minutes after reaching 220 °C. The phenol vapor by-produced during the polymerization reaction was introduced into a reflux condenser at 100 °C, and a certain amount of monomer components contained in the phenol vapor were returned to the reactor, while the uncondensed phenol vapor was introduced into a condenser at 45 °C for recovery. After introducing nitrogen into the first reactor to temporarily return to atmospheric pressure, the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Then, the temperature increase and decompression inside the second reactor were started, and the internal temperature reached 240 °C and the pressure reached 0.2 kPa in 50 minutes. Then, polymerization was carried out until a given stirring power was reached. At the moment when the given power was reached, nitrogen was introduced into the reactor to restore the pressure, and the produced polyester carbonate resin was extruded into water, and the wire was cut to obtain pellets.
[0237] 2-2. Fabrication of the retardation film
[0238] After vacuum drying the obtained polyester carbonate resin (pellets) at 80 °C for 5 hours, a strip-shaped resin film with a thickness of 135 μm was fabricated using a film-forming apparatus equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder set temperature: 250 °C), a T-die (width 200 mm, set temperature: 250 °C), a chill roll (set temperature: 120 - 130 °C), and a winder. The obtained strip-shaped resin film was stretched in the width direction at a stretching temperature of 133 °C and a stretching ratio of 2.8 times to obtain a retardation film with a thickness of 53 μm. The obtained retardation film had Re(550) of 141 nm, Re(450) / Re(550) of 0.82, and an Nz coefficient of 1.12.
[0239] 3. Fabrication of the polarizer with a retardation layer
[0240] On the surface of the polarizing film of the polarizer obtained in the above 1., the retardation film obtained in the above 2. was adhered using an acrylic adhesive (thickness: 5 μm). At this time, the adhesion was performed in such a manner that the absorption axis of the polarizing film and the slow axis of the retardation film formed an angle of 45°. In this way, a polarizer with a phase difference layer having a structure of a protective layer / adhesive layer / polarizing film / adhesive layer / phase difference layer was obtained. The total thickness of the obtained polarizer with a phase difference layer was 89 μm. The obtained polarizer with a phase difference layer was subjected to the evaluations in the above (6) and (7).
[0241] The structures and the respective evaluation results of the polarizers with a phase difference layer obtained in Examples 1 to 3 and Comparative Examples 1 and 3 are shown in Table 2.
[0242]
[0243] [Evaluation]
[0244] From Table 2 and the comparison between Example 1 and Comparative Example 2, it is clear that the polarizer with a phase difference layer of the example of the present invention is thin, can suppress warping after the heating test, and has excellent optical characteristics. In addition, by making the weight per unit area of the polarizer with a phase difference layer below a given value, the bending resistance is improved.
[0245] Industrial Applicability
[0246] The polarizer with a phase difference layer of the present invention can be suitably used as a circular polarizer for a liquid crystal display device, an organic EL display device, and an inorganic EL display device.
Claims
1. A manufacturing method of a polarizer with a retardation layer, The polarizer with a retardation layer has a polarizer and a retardation layer. The polarizer includes a polarizing film and a protective layer provided on at least one side of the polarizing film. The polarizing film is composed of a polyvinyl alcohol resin film containing a dichroic substance, has a thickness of 8 μm or less, a monomer transmittance of 43.5% or more, and a degree of polarization of 99.940% or more. The retardation layer is an alignment fixing layer of a liquid crystal compound. The total thickness of the polarizer with a retardation layer is 28 - 52 μm. This manufacturing method includes manufacturing the above-mentioned polarizing film through the following manufacturing method, and the manufacturing method includes: Forming a polyvinyl alcohol resin layer containing an iodide or sodium chloride and a polyvinyl alcohol resin on one side of a strip-shaped thermoplastic resin substrate to form a laminate; and Successively performing an auxiliary stretching treatment in a gas atmosphere, a dyeing treatment, a stretching treatment in an aqueous solution, and a drying shrinkage treatment of heating while transporting in the length direction to cause a 2% - 10% shrinkage in the width direction. In the drying shrinkage treatment, a heating roller is used in a heating furnace, and the total contact time of the laminate with the heating roller is 1 - 20 seconds.
2. The manufacturing method of a polarizer with a retardation layer according to claim 1, wherein, The retardation layer is a single layer of an alignment fixing layer of a liquid crystal compound, wherein Re(550) of the retardation layer is 100 nm to 190 nm, and the angle formed by the slow axis of the retardation layer and the absorption axis of the polarizing film is 40° to 50°.
3. The manufacturing method of a polarizer with a retardation layer according to claim 1, wherein, The retardation layer has a laminated structure of an alignment fixing layer of a first liquid crystal compound and an alignment fixing layer of a second liquid crystal compound, wherein Re(550) of the alignment fixing layer of the first liquid crystal compound is 200 nm to 300 nm, and the angle formed by the slow axis thereof and the absorption axis of the polarizing film is 10° to 20°, and Re(550) of the alignment fixing layer of the second liquid crystal compound is 100 nm to 190 nm, and the angle formed by the slow axis thereof and the absorption axis of the polarizing film is 70° to 80°.
4. The manufacturing method of a polarizer with a retardation layer according to any one of claims 1 - 3, wherein, The monomer transmittance of the polarizing film within a region of 50 cm 2 has a difference between the maximum value and the minimum value of 0.15% or less.
5. The manufacturing method of a polarizer with a retardation layer according to any one of claims 1 - 3, wherein, The width of the polarizing film is 1000 mm or more, and the difference between the maximum value and the minimum value of the monomer transmittance at positions along the width direction of the polarizing film is 0.3% or less.
6. The manufacturing method of a polarizer with a retardation layer according to any one of claims 1 - 5, wherein, The monomer transmittance of the polarizing film is 44.0% or less, and the degree of polarization is 99.990% or less.
7. The manufacturing method of a polarizer with a retardation layer according to any one of claims 1 - 6, wherein the polarizer with a retardation layer further has another retardation layer outside the retardation layer. The method further includes a step of providing another retardation layer outside the retardation layer, and the refractive index characteristics of the another retardation layer exhibit a relationship of nz > nx = ny.
8. The method for manufacturing a polarizing plate with a retardation layer according to any one of claims 1 to 7, wherein the polarizing plate with a retardation layer further has a conductive layer or an isotropic substrate with a conductive layer outside the retardation layer, The method further includes a step of providing a conductive layer or an isotropic substrate with a conductive layer outside the retardation layer.
Citation Information
Patent Citations
Liq. crystalline (LC) material
DE19504224A1
Novel polymerizable liquid crystalline compounds
DE4408171A1
Liquid crystalline reticulated polysiloxanes
EP0066137A1
Picture display cell, method of forming an orientation layer on a substrate of the picture display cell and monomeric compounds for use in the orientation layer
EP0261712A1
Liquid crystal polyorganosiloxanes containing (meth)acryloxy groups
EP0358208A2